Choice of antifibrotic medication and disease severity predict weight loss in idiopathic pulmonary fibrosis. (December 2019) - Perelas, Apostolos; Glennie, Jessica; van Kerkhove, Karen; Li, Manshi; Scheraga, Rachel G.; Olman, Mitchell A.; Culver, Daniel A.
Abstract: Purpose: Although safety and tolerability of approved antifibrotics has been reported extensively, little is known about their effects on weight. We analyzed predictors of weight change after one year of uninterrupted antifibrotic therapy in patients followed at our institution's interstitial lung disease clinic. Methods/Results: We identified 80 patients on antifibrotic therapy (44 pirfenidone/36 nintedanib) with at least one year of follow-up and no therapy interruptions. Thirty-five patients (44%) lost more than 5% of their baseline body weight, and 11 (19%) lost more than 10%. A higher proportion of patients on nintedanib experienced a clinically significant weight loss (>5%) versus pirfenidone (61% vs 30%, p = 0.005). Univariate and multivariate analyses identified nintedanib therapy and a higher composite physiologic index (CPI) as predictors of weight loss. Conclusions: Weight loss is common among IPF patients on antifibrotic therapy. Nintedanib therapy and more advanced disease were identified as predictors of weight loss in this population.